Agricultural Resource Sharing And Crop Management - et. al., Arvind Kumar G, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, agricultural resource sharing and the best suitable crop prediction has been considered. Four-Wheel Robo is built that can move in agricultural fields and the NPK sensor is attached to it which can be controlled using a remote desktop. To get the soil data, the sensor is inserted into the soil with the help of a gear motor and controlled using IR sensors. NPK sensor gives the nitrogen, phosphorous, and potassium values in ppm. The values from the NPK sensor and actual NPK values for each soil got from search engines and websites are compared and the nearest value is mapped, doing this best suitable crop is predicted. The data from the sensor is also stored and accessed from the firebase cloud. .For agricultural resource sharing android application has been built through android studio IDE. The application consists of categories like types of machinery, saplings, seeds, empty fields, laborers, and fertilizers. An application can be differentiated into two parts owner and tenant. The owner uploads the resources that are not currently required to him and the tenant uses the resources by paying the owner with some adequate amount as mentioned by the owner. So, the android application behaves like a platform between owner and tenant. The processor used to process the sensor data, predict the best suitable crop and uploaded it to Firebase cloud using an internet connection. The latest NPK commercial crop and fruit data can be seen in the android application with GPS (latitude and longitude) values.